Impact of the hinge region L38↑H↑L double insertion mutation on the structure and function of the HIV-1 South African subtype C protease - Setshedi, Mpho (My University, 2022)
The development of mutations in the human immunodeficiency virus (HIV) genome has become a crucial factor in limiting antiretroviral therapy for HIV/AIDS treatment. By the end of June 2021, approximately 37 million people globally were infected with HIV. South Africa, in particular, bears the brunt of the HIV-1 subtype C epidemic with 7.7 million infections. The HIV protease is a homodimeric protein that naturally contains 99 amino acids per monomeric subunit. The protease is vital in the HIV life cycle because it cleaves Gag and Gag-Pol precursor polyproteins into proteins necessary for viral assembly, maturation, and infection. Herein, we performed a comparative study between the HIV-1 subtype C protease (wild-type) and a protease containing a double amino acid insertion (histidine and leucine at codon 38), L38↑H↑L. Each recombinant protease was overexpressed and isolated from E. coli BL21 (DE3) pLysS cells, and purified using ion-exchange chromatography. Far-UV circular dichroism spectra of the WT-CSA and L38↑H↑L protease displayed a minimum at 218 nm which was indicative of a predominantly beta-sheeted protein. Size exclusion chromatography results indicated that the L38↑H↑L protease has a homodimeric molecular weight of approximately 22 kDa which is consistent with characteristics pertaining to the WTCSA protease. Steady-state enzyme kinetic assays were performed by using a fluorogenic substrate that mimics a cleavage site on the Gag polyprotein. The L38↑H↑L protease displayed a 15-fold reduction in KM and a 1.25-fold reduction in the catalytic turnover number, kcat relavite to the WT-CSA protease. The L38↑H↑L protease was found to be 11 times more efficient in catalyzing the hydrolysis of the fluorogenic substrate relative to the WT-CSA protease. The L38↑H↑L protease displayed a 2.25-fold and 0.71-fold reduction in VMax and specific activity relative to the WT-CSA protease. The data suggested that amino acids in the hinge region of HIV-1 proteases indirectly affect enzyme catalysis and substrate specificity but has no effect on the structural stability of the L38↑H↑L protease. Enzyme inhibition studies in the presence of Saquinavir, Darunavir and Atazanavir showed that the L38↑H↑L binds the inhibitors more tightly relative to the WT-CSA protease. This was confirmed by the lower IC50 concentrations of the respective protease inhibitors relative to the WT-CSA protease. Thermodynamics data obtained from performing displacement isothermal titration calorimetry showed that the L38↑H↑L protease displayed a 2-fold increase (-79.02 ± 6.81 kJ/mol) in ∆H when bound to Atazanavir and a 1-fold reduction in ∆H when bound to ii Saquinavir (-9.35 ±3.1 kJ/mol) and Darunavir (-27.61 ± 1.76 kJ/mol) relative to the WT-CSA protease. The binding of Saquinavir and Darunavir to the L38↑H↑L protease was found to be entropically unfavourable (where -T∆S was -32.81 ± 6.40 kJ/mol and -22.74 ± 3.70 kJ/mol, respectively), whereas the binding of the protease to Atazanavir was entropically unfavourable (-T∆S was 37 ± 4.83 kJ/mol). Upon analysis of the Kd, it was noted that L38↑H↑L protease displayed a 2-fold increased drug susceptibility towards Saquinavir (79 ± 7.50 nM), and 2-fold reduced drug susceptibility towards Atazanavir (83.63 ± 7.10 nM), while the drug susceptibility for Darunavir (3.3 ± 1.20 nM) remained unchanged relative to the WT-CSA protease. Due to the important role of the hinge and flap region in accommodating substrates and inhibitors into the active site of the protease, the mutations affected the kinetics of substrate hydrolysis and the thermodynamics of drug binding
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Human Immunodeficiency Virus (HIV); HIV-1 subtype C; Antiretroviral